Collaborative demand response in smart electric grid with virtual system operator. Issue 3 (21st August 2018) - Yammani, Chandrasekhar; Prabhat, Pankaj
Abstract : The authors present a novel concept of virtual system operator (VSO) and its mechanism. This mechanism aims to determine load consumption pattern on day‐ahead basis which suits all the involved entities individually in real‐time pricing environment. The demand profile is scheduled by every consumer by performing demand response (DR) without having to coordinate with other consumers in the system. In the process flow, the VSO which remains in communication with the system operator and the consumer relays information regarding day‐ahead electricity tariff to consumers. Based on which the consumers simultaneously perform DR to optimise their electricity bill and forward the schedule to the VSO. This process repeats iteratively until a balanced price profile as well as load schedule is established in the system. Such schedules are capable of reducing dynamics in the electricity market. The proposed concept is demonstrated through three different types of consumers. These consumers realise DR through different objective functions and up to different extents. Ultimately, the load schedules are obtained for all individual users and corresponding price profile which suits every entity of the system.